Survival Profile and Prognostic Factors for Appendiceal Mixed Neuroendocrine Non-neuroendocrine Neoplasms: A SEER Population-Based Study - Zheng, Mengzhen; Li, Tong; Li, Yan; Zhang, Tengfei; Zhang, Lianfeng; Ma, Wang; Zhou, Lin (Frontiers in Oncology, 2020)
Introduction: Mixed neuroendocrine non-neuroendocrine neoplasm (MiNEN) is a rare form of neuroendocrine neoplasms. The purpose of this study was to investigate the characteristics and survival profile of appendiceal MiNENs, with a view of providing robust clinical features of this rare disease. Methods: Patients were selected from the Surveillance, Epidemiology and End Results database (2004-2016). The prognosis of MiNEN (n=315) was compared with other histological subtypes including neuroendocrine tumor (n=1734), neuroendocrine carcinoma (n=375), goblet cell carcinoid (n=968), signet ring cell carcinoma (n=463), mucinous adenocarcinoma (n=2355) and non-mucinous adenocarcinoma (n=1187) in the appendix. Age-adjusted incidence was calculated using Joinpoint regression. The Cox proportional hazards model and the Fine-Gray competing risk model were used to perform overall survival (OS) and cancer-specific mortality (CSM) analyses, respectively. Results: The age-adjusted incidence of MiNENs increased from 0.01/100,000 person-years in 2004 to 0.07/100,000 person-years in 2016. The 3-, 5-, and 10-year OS rates for MiNENs were 69.5%, 57.4% and 43.7%, respectively, and the corresponding CSM rates were 23.1%, 36.4% and 45.1%, respectively. Multivariate analysis revealed that the prognosis of MiNENs was worse than that of neuroendocrine tumors, neuroendocrine carcinoma, goblet cell carcinoid and mucinous adenocarcinoma but better than that of non-mucinous adenocarcinoma and signet ring cell carcinoma. Tumor extension was the only independent factor influencing the prognosis of MiNENs, but tumor size, grade and surgical approaches were not. Moreover, when compared with local excision or appendectomy, extensive surgery such as hemicolectomy or colectomy did not prolong the survival of individuals with MiNENs. Conclusion: MiNEN is a rare but aggressive tumor with a poor prognosis differing from neuroendocrine neoplasms, goblet cell carcinoid and adenocarcinomas. To improve the prognosis of the disease, early diagnosis and comprehensive evaluation are necessary.